Overexpression of Protein Kinase C iota as a prognostic marker and its role in oxaliplatin resistance in colorectal cancer - Xuankai Liao; Mengyuan Liu; Chunli Hong; Yuyan Liu; Qing Li; Ying Chen; Tingzhen Zhang; Hongda Chen; Shuying Fu (BMC Gastroenterology)
Abstract Background Protein Kinase C iota (PKCι) has been implicated in cancer progression and chemoresistance, but its prognostic significance in solid tumors remains unclear. This study aimed to evaluate the expression of PKCι in tumor tissues and its association with clinicopathological features, survival outcomes, and chemotherapy response in patients with cancer. Methods A retrospective analysis was conducted on patients with confirmed cancer diagnoses. Immunohistochemistry (IHC) was used to assess PKCι expression levels in tumor tissues. Kaplan-Meier survival curves and univariate Cox analysis were applied to evaluate the impact of PKCι expression and other clinicopathological variables on overall survival (OS) and progression-free survival (PFS). The association between PKCι expression and chemotherapy resistance, particularly oxaliplatin resistance, was also investigated. Results PKCι overexpression was possibly correlated with advanced clinical stage, metastasis, organs involvement, vascular invasion, and perineural invasion. Patients with PKCι overexpression was possibly correlated with oxaliplatin resistance(P = 0.014). Besides, Patients with PKCι overexpression exhibited significantly shorter PFS compared to those with low expression levels (P = 0.0006). Univariate Cox analysis confirmed that metastasis (H.R. = 11.910, P = 0.018) and clinical staging (H.R. = 5.498, P = 0.027) were independent prognostic factors for OS, whereas CEA levels (H.R. = 3.497, P = 0.005) was independent predictors of PFS. Conclusion PKCι overexpression is associated with tumor aggressiveness and chemotherapy resistance, indicating its potential as a prognostic biomarker and therapeutic target in cancer preliminarily.